Interpersonal Communication among Athletes and Badminton Coaches at Irwan Badminton Academy Executive Board - Made Dinda Windiasari; Teguh Dwi Putranto (Journal Coaching Education Sports, 2024)
Background Problems: Communication between coaches and athletes has an important role in achieving goals in sports, both during training and competition. One form of communication applied between coaches and athletes is interpersonal communication. This research focuses on interpersonal communication, where in interpersonal communication there are lime main elements which include openness, empathy, support, positive attitude, and common goals. Each element contributes to building effective communication, strengthening motivation, and creating a training environment that supports the holistic development of athletes. Research Objectives: This study aims to determine how interpersonal communication between athletes and coaches at the Irwan Badminton Academy. Methods: This research is a descriptive qualitative approach. The collection method uses interviews, observation, and documentation. The informants in this study amounted to 13 consisting of 3 coaches, 5 man athletes, and 5 woman athletes at Irwan Badminton Academy Executive Board. Findings/Results: The results show that a healthy and productive relationship between coaches and athletes not only affects athletes' performance on the field, but also shapes athletes' character and mental resilience. Conclusion: Interpersonal communication that occurs between coaches and athletes goes well, so the opportunity for athletes to achieve achievements would be even greater. This is also evident from the results of observations and interviews, that athletes can show and improve their training performance, and the spirit of motivation that can always be maintained.